SPECIAL EDUCATION: MODERN APPROACHES TO TRAINING SPECIALISTS CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Naboka, O.; Tatianchikova, I. (Physical and Mathematical Education, 2021)
Problem formulation. The article reveals modern approaches to professional training for the education of children with special educational needs. It is noted that in the context of socio-economic changes in society, new views on the quality of education in general, there is a need to reform and modernize the basic provisions of special education, which requires its compliance with European and new state standards in Ukraine. Materials and methods. To determine modern approaches to the training of specialists for the education of children with special educational needs in the study were the use of theoretical methods: analysis, generalization, interpretation of modern scientific and educational literature. Results. The results substantiate the need for systematic, gradual and consistent special pedagogical work aimed at developing social activity, educating the viability of the individual through the formation of vital competencies, which will ensure the full existence of a child with special educational needs in society. The main components of the new Concept of special education are identified: inclusive form of education of children with special needs, ensuring their socialization, personality-oriented and competence-based approaches. The focus is on a number of issues that are still unresolved and hamper the training of children with special educational needs, including in an inclusive education institution. Conclusions. The results of the theoretical study proved the need for training for the rehabilitation of children in a broad sense. The idea of independent living, which is the core of the modern Concept of special education, is highlighted. It is emphasized that specialists of special educational institutions should play an important role in managing the process of social development of their pupils and achieving a general level of social persuasion. The need to introduce innovative approaches to the training of specialists for the education of children with special needs is noted.